2007
DOI: 10.1103/physreva.76.042313
|View full text |Cite|
|
Sign up to set email alerts
|

Entanglement invariant for the double Jaynes-Cummings model

Abstract: We study entanglement dynamics between four qubits interacting through two isolated Jaynes-Cummings hamiltonians, via the entanglement measure based on the wedge product. We compare the results with similar results obtained using bipartite concurrence resulting in what is referred to as "entanglement sudden death". We find a natural entanglement invariant under evolution demonstrating that entanglement sudden death is caused by ignoring (tracing over) some of the system's degrees of freedom that become entangl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 27 publications
3
64
2
Order By: Relevance
“…Using this model the so called sudden death effect is found as a result of the time-evolution of the system [34] (see also [35]). Although these results were immediately generalized to the case of six pairwise concurrences [36], the constraint of having no more than one photon in the cavities was preserved; similar results can be found in [37]. The case of an imperfect matching of the atoms to the cavity fields has been also analyzed in connection to the entanglement evolution [38].…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Using this model the so called sudden death effect is found as a result of the time-evolution of the system [34] (see also [35]). Although these results were immediately generalized to the case of six pairwise concurrences [36], the constraint of having no more than one photon in the cavities was preserved; similar results can be found in [37]. The case of an imperfect matching of the atoms to the cavity fields has been also analyzed in connection to the entanglement evolution [38].…”
Section: Introductionmentioning
confidence: 64%
“…In contrast with other approaches already reported (see e.g. [34][35][36][37][38][39]), the present work provides an analysis of the bipartite atomic concurrence when the initial field state in each of the cavities is not longer the vacuum or the single photon state but an arbitrary Fock state. We have found that the entanglement of the atoms depends on the initial number of photons that integrate the radiation baths in the cavities.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Remarkably, they find that even when there is no interaction (either directly or through a correlated environment), there are certain states whose entanglement decays exponentially with time, while for other closely related states, the entanglement vanishes completely in a finite time. This phenomenon, called entanglement sudden death (ESD), has been well explored in the case of bipartite systems and there are a number of studies looking at ESD in multipartite systems [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%